1980
DOI: 10.2307/1935178
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Decomposition of Roots and Rhizomes of Two Tidal Marsh Plants

Abstract: In situ decomposition of roots and rhizomes of the marsh plants, Juncus roemerianus and Spartina cynosuroides was investigated using litter bags. The decomposition rate was greatest in the top 10 cm (20% mass loss/yr) of the marsh soil. There was no apparent decomposition below 20 cm depth. Belowground tissues of S. cynosuroides decomposed faster than those of J. roemerianus during the first 4 mo. The rhizome decomposition rate of 27%/yr (mass loss) was faster than the 16%/yr of the roots of J. reomerianus. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1

Year Published

1984
1984
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 15 publications
4
43
1
Order By: Relevance
“…Temperature has been shown to strongly influence rates of microbial degradation of Spartina in salt-marsh sediments (Benner et al 1986a), but in the present study temporal changes in chemical composition and decomposability confound the seasonal influence of temperature on rates of weight loss. Overall rates of belowground decomposition (55% AFDW loss in 1.5 yr) in the present study were relatively high compared to other studies of belowground decomposition of salt-marsh vegetation (Buth 1987;Hackney and de la Cruz 1980;Valiela et al 1984).…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…Temperature has been shown to strongly influence rates of microbial degradation of Spartina in salt-marsh sediments (Benner et al 1986a), but in the present study temporal changes in chemical composition and decomposability confound the seasonal influence of temperature on rates of weight loss. Overall rates of belowground decomposition (55% AFDW loss in 1.5 yr) in the present study were relatively high compared to other studies of belowground decomposition of salt-marsh vegetation (Buth 1987;Hackney and de la Cruz 1980;Valiela et al 1984).…”
Section: Resultscontrasting
confidence: 63%
“…Rates of decomposition in sediments could therefore be quite variable, particularly in areas where molecular oxygen is available as a terminal electron acceptor, such as fiddler crab burrows and the oxidized regions surrounding living rhizome and root biomass. Hackney and de la Cruz (1980) found that rates of belowground decomposition of Spartina were about threefold higher at 5-than at 15-cm depth in marsh sediments.…”
Section: Resultsmentioning
confidence: 97%
“…We can only speculate about the factors controlling the depth distribution of marsh grass roots and rhizomes. The deeper distribution of dead material than of biomass may reflect the lower rate of microbial activity at depth in marsh sediments (Christian and Wiebe 1978;Howarth and Hobbie 1982) and hence a decreased rate of decomposition (Hackney and de la Cruz 1980). Live material may be centered nearer the surface, where remineralization and supposedly nutrient supply are greatest, but deep enough to avoid damage clue to seasonal changes in microclimatology.…”
Section: Resultsmentioning
confidence: 99%
“…The cores were replaced in their original position with individual litterbags inserted horizontally at the 30, 15 and 3 cm depth levels (cf. Hackney & de la Cruz 1980). A 4th litterbag was placed above-ground on top of each core.…”
Section: Methodsmentioning
confidence: 99%